2014
DOI: 10.1002/prot.24642
|View full text |Cite
|
Sign up to set email alerts
|

Computational identification of post-translational modification-based nuclear import regulations by characterizing nuclear localization signal-import receptor interaction

Abstract: The binding affinity between a nuclear localization signal (NLS) and its import receptor is closely related to corresponding nuclear import activity. PTM-based modulation of the NLS binding affinity to the import receptor is one of the most understood mechanisms to regulate nuclear import of proteins. However, identification of such regulation mechanisms is challenging due to the difficulty of assessing the impact of PTM on corresponding nuclear import activities. In this study we proposed NIpredict, an effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…NLS signals tend to be conserved between proteins, and are thus sensitive to alterations [13] . Our previous study has shown that phosphorylation on NLS residues has a dramatic impact on the binding ability of nuclear proteins to nuclear import receptors, and therefore affects nuclear localization efficiency [8] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NLS signals tend to be conserved between proteins, and are thus sensitive to alterations [13] . Our previous study has shown that phosphorylation on NLS residues has a dramatic impact on the binding ability of nuclear proteins to nuclear import receptors, and therefore affects nuclear localization efficiency [8] .…”
Section: Resultsmentioning
confidence: 99%
“…Post-transcriptional modification (PTM)-based modulation of the NLS binding affinity to import receptors is one of the most understood mechanisms that regulates the nuclear import of proteins [4][5][6][7] . Our previous study has developed an effective algorithm to predict nuclear import activity, in which molecular interaction energy components (MIECs) were used to characterize NLS-import receptor interaction, and a support vector regression machine(SVR) was used to learn the relationship between the characterized NLS-import receptor interaction and the corresponding nuclear import activity [8] . Based on our model, we developed a systematic framework to precisely predict how potential PTM, such as phosphorylation, regulates nuclear import of human and yeast nuclear proteins.…”
Section: Introductionmentioning
confidence: 99%
“…NLS is a polybasic sequence comprised of multiple lysines (K) or arginines (R). Lin et al (2014) showed that template PxxK [KR] x [KR]xx (a very common NLS motif) may have many modifications and depended on binding affinity to its import receptor, and it can potentially have different nuclear import activity. Exon 1 of Rheb1 presents in both wild-type Rheb1 and mutant Rheb1/β-gal gene of our experimental mice.…”
Section: Discussionmentioning
confidence: 99%